Analisis Perbandingan Elemen Magis dalam Dongeng Korea ‘Ureong Gaksi (우렁 각시)’ dan Dongeng Indonesia ‘Keong Emas’ - Nadhira, Rizqi Hauna; Samsudin, Didin; Azizah, Asma (Universitas Gadjah Mada, 2025)
Numerous folktales across global literature exhibit notable parallels, such as the Korean story Ureong Gaksi (우렁각시) and the Indonesian legend Keong Emas. This study examines the structural features of both narratives by analyzing their intrinsic elements through Claude Lévi-Strauss’s structuralism and classifying their magical components using Wendy B. Faris’s framework of magical realism. The primary sources are the picture-book versions of Ureong Gaksi by Han Seong-ok (한성옥) and Keong Emas by Tira Ikranegara. A descriptive–qualitative comparative method facilitates an in-depth examination and comparison of the two texts. Data are collected through library research and analyzed to identify structural similarities and differences. Findings indicate that both tales share a central theme but differ in character portrayal, setting, and plot development. Through Lévi-Strauss’s structuralist approach, six fundamental mythemes related to magical elements are identified and subsequently mapped onto Faris’s five features of magical realism: (1) irreducible element, (2) phenomenal world, (3) merging of realms, (4) unsettling doubt, and (5) disruptions of time, space, and identity. The analysis demonstrates that, while both stories incorporate supernatural figures and magical motifs, they display distinct structural patterns, particularly in their characters, supporting figures, and types of conflict. Nevertheless, each narrative fulfills all five of Faris’s criteria for magical realism.